Contribution of Leg Muscle Explosive Power and Eye-Hand Coordination to The Accuracy Smash of Athletes in Volleyball Club of Universitas Islam Riau - Yulianti, Mimi (Universitas Negeri Semarang, 2017)
The purpose of this study was to determine the contribution of leg muscle explosive power and eye-hand coordination. The type of research was correlational. The population in this study was all athletes who actively follow the training as many as 20 people and using total sampling technique. Thus the sample in this study amounted to 20 men athletes. The data were collected using the measurement test on the three variables: the leg muscle explosive power data was using vertical jump test, eyehand coordination was using ballwerfen und fangen test and smash accuracy was using smash accuracy test. The data were analyzed by product moment correlation and double correlation and then continued with contribution of the determinant formula. Based on data analysis found that there was contribution of leg muscle explosive power equal to 35,52%, eye-hand coordination equal to 20,79%, and both equal to 40,70% regarding to the accuracy smash of volleyball atletes of Universitas Islam Riau. It was concluded that there was contribution of leg muscle explosive power and eye-hand coordination to the smash accuracy of volleyball athlete of Universitas Islam Riau.